Bioactive snail mucus-slime extract loaded chitosan scaffolds for hard tissue regeneration: the effect of mucoadhesive and antibacterial extracts on physical characteristics and bioactivity of chitosan matrix. (22nd September 2021) - Perpelek, Merve; Tamburaci, Sedef; Aydemir, Selma; Tihminlioglu, Funda; Baykara, Basak; Karakasli, Ahmet; Havitcioglu, Hasan
Abstract: Biobased extracts comprise various bioactive components and they are widely used in tissue engineering applications to increase bioactivity as well as physical characteristics of biomaterials. Among animal sources, garden snail Helix aspersa has come into prominence with its antibacterial and regenerative extracts and show potential in tissue regeneration. Thus, in this study, bioactive H. aspersa extracts (slime, mucus) were loaded in chitosan (CHI) matrix to fabricate porous scaffolds for hard tissue regeneration. Physical, chemical properties, antimicrobial activity was determined as well as in vitro bioactivity for bone and cartilage regeneration. Mucus and slime incorporation enhanced mechanical properties and biodegradation rate of CHI matrix. Scanning electron microscopy images showed that the average pore size of the scaffolds decreased with higher extract content. Mucus and slime extracts showed antimicrobial effect on two bacterial strains. In vitro cytotoxicity, osteogenic and chondrogenic activity of the scaffolds were evaluated with Saos-2 and SW1353 cell lines in terms of Alkaline phosphatase activity, biomineralization, GAG, COMP and hydroxyproline content. Cell viability results showed that extracts had a proliferative effect on Saos-2 and SW1353 cells when compared to the control group. Mucus and slime extract loading increased osteogenic and chondrogenic activity. Thus, the bioactive extract loaded CHI scaffolds showed potential for bone and cartilage regeneration with enhanced physical properties and in vitro bioactivity.